PENGARUH TERAPI RELAKSASI BENSON TERHADAP CEMAS PASIEN PRE OPERASI RUANGAN IBS RSUD KARANGANYAR - Agus Suseno; Estu Nugrahaning Widi; Siti Aisah; Aric Vranada (CV. Publikasi Indonesia, 2025)
Surgery or surgical procedure is a medical procedure performed on the body to improve physical function. This mechanism is a form of medical treatment that can cause feelings of fear, anxiety, and worry. The pre-surgical concept is part of perioperative nursing and initial preparation before entering the operating room. During this period, patients generally experience psychological changes such as feelings of anxiety, fear, and stress. Feelings of anxiety can lead to an unstable condition characterized by increased blood pressure, pulse, and respiratory rate. During this period, patients generally experience psychological changes such as feelings of anxiety, fear, and stress. Feelings of anxiety can lead to an unstable condition characterized by increased blood pressure, pulse, respiratory rate, nausea/vomiting, and restlessness, which will interfere with the surgical process. One nursing intervention that can be done to reduce anxiety is Benson's relaxation therapy. The purpose of this study was to determine the results of the application of Benson relaxation therapy in reducing the anxiety level of preoperative patients. This final scientific research is a descriptive study in the form of a case study conducted in the IBS room of the Karanganyar Regional General Hospital. The subject of this case study was one pre-operative patient with anxiety. The subject of this case study was one pre-operative patient with anxiety. This therapy pen is performed using the Benson Relaxation Therapy Standard Operating Procedure (SOP) and the measurement of the patient's anxiety level using the Hamilton Anxiety Rating Scale (HARS). The conclusion drawn is that Benson's relaxation therapy is effective in reducing preoperative anxiety levels in patients. This is evidenced by the results of the measurement of anxiety levels before therapy, which showed a score of 25 (moderate anxiety), and after therapy, which decreased to a score of 17 (mild anxiety).